Research Advances on Therapeutic Approaches to Congenital Central Hypoventilation Syndrome (CCHS) - Di Lascio, Simona; Benfante, Roberta; Cardani, Silvia; Fornasari, Diego (Frontiers in Neuroscience, 2021)
Congenital central hypoventilation syndrome (CCHS) is a rare life-long genetic disorder characterized by the failure of autonomic control of breathing, and so far has no curative treatment. Most CCHS patients have heterozygous mutations in the PHOX2B gene, that encodes a key transcription factor in the development (and maintenance) of the autonomic nervous system, and in particular the neuronal structures involved in respiratory reflexes. The underlying pathogenetic mechanism is still unclear, although studies in vivo and in CCHS patients indicate that some neuronal structures may be damaged. Moreover, in vitro studies of cell models of CCHS suggest that transcriptional dysregulation and protein misfolding may be key pathogenic mechanisms. This review summarizes recent progress in our understanding of the molecular pathogenesis of this complex disease and discusses the development of therapeutic research in the light of the new insights into the function of PHOX2B.